Camel Streptococcus agalactiae populations are associated with specific disease complexes and acquired the tetracycline resistance gene tetM via a Tn916-like element - Fischer, A.; Liljander, Anne M.; Kaspar, H.; Muriuki, C.; Fuxelius, H.H.; Bongcam-Rudloff, E.; Villiers, Etienne P. de; Huber, C.A.; Frey, J.; Daubenberger, C.A.; Bishop, Richard P.; Younan, M.; et al. (Springer, 2013)
Camels are the most valuable livestock species in the Horn of Africa and play a pivotal role in the nutritional sustainability for millions of people. Their health status is therefore of utmost importance for the people living in this region. Streptococcus agalactiae, a Group B Streptococcus (GBS), is an important camel pathogen. Here we present the first epidemiological study based on genetic and phenotypic data from African camel derived GBS. Ninety-two GBS were characterized using multilocus sequence typing (MLST), capsular polysaccharide typing and in vitro antimicrobial susceptibility testing. We analysed the GBS using Bayesian linkage, phylogenetic and minimum spanning tree analyses and compared them with human GBS from East Africa in order to investigate the level of genetic exchange between GBS populations in the region. Camel GBS sequence types (STs) were distinct from other STs reported so far. We mapped specific STs and capsular types to major disease complexes caused by GBS. Widespread resistance (34%) to tetracycline was associated with acquisition of the tetM gene that is carried on a Tn916-like element, and observed primarily among GBS isolated from mastitis. The presence of tetM within different MLST clades suggests acquisition on multiple occasions. Wound infections and mastitis in camels associated with GBS are widespread and should ideally be treated with antimicrobials other than tetracycline in East Africa.